Challenges in breast cancer genetic testing. A call for novel forms of multidisciplinary care and long-term evaluation. (August 2022) - Menko, Fred H.; Monkhorst, Kim; Hogervorst, Frans B.L.; Rosenberg, Efraim H.; Adank, Muriel A.; Ruijs, Mariëlle W.G.; Bleiker, Eveline M.A.; Sonke, Gabe S.; Russell, Nicola S.; Oldenburg, Hester S.A.; van der Kolk, Lizet E.
Abstract: Current methods of next generation sequencing may simultaneously detect multiple germline breast cancer susceptibility variants. However, it is a challenge to maximize the clinical benefit of genetic analysis for patients and family members while minimizing potentially harmful effects. Relevant issues include criteria for referral, the choice of gene panel, handling of variants of unknown significance, cancer risk counselling in clinical context including family history data, risks of tumours other than breast cancer, handling of potential germline findings revealed by tumour testing and the clinical management of gene variant carriers, including surveillance, targeted therapy, radiotherapy and risk-reducing surgery. We outline current challenges in the field of breast cancer genetics and call for novel forms of multidisciplinary care and long-term evaluation. Graphical Abstract: ga1 Highlights: Next generation sequencing allows detailed analysis of cancer predisposition genes. Implementation of NGS requires multidisciplinary care and novel forms of organization. Optimal management of mutation carriers is an important future goal. Long-term evaluation of novel diagnostic and management procedures is essential.